NCOG-61. A CASE OF LONG TERM SURVIVOR OF DISSEMINATED AND RELAPSED GERMINOMA. EIGHTEEN YEARS OF FOLLOW UP - Fujimaki, Takamitsu (Neuro Oncol, 2020)
Germinomas will respond to first-line treatment in general, but prognoses of disseminated and/or relapsed disease are sometimes poor and detailed course of those patients are not well documented. Here we report one of such cases. PATIENT: A 35-year-old man (at the time of abstract submission) initially had polyuria at the age of 15 and anorexia at 16. At the age of 17, MRI showed neurohypophyseal and disseminated tumor along lateral ventricular walls. He was diagnosed to have germinoma by partial resection of the tumor. ICE (Ifosfamide, Cisplatin, Etoposide) chemotherapy was given followed by 24 Gy whole ventricular irradiation. The tumor was well controlled for 22 months. However despite maintenance ICE chemotherapy, the tumor relapsed along the ventricular walls. With simultaneous BEP (Bleomycin, Etoposide, Cisplatin) chemotherapy and 40 Gy whole neuroaxis irradiation, all the tumor disappeared and he remains in complete remission now. He is receiving hormone replacement therapy. Eight years after the initial surgery, an MRI showed cavernous angioma in the cerebellum and the number has been increasing in follow-up scans. Asymptomatic minor bleeding occurred 14 and 15 years after the initial surgery. On MRA, no vasculopathy on major vessels has been identified. His wife gave birth to his first child through infertility treatment, when he was 34. He finished graduate school to obtain master degree and working as a company employee. CONCLUSION: Germinoma is a disease that can cause long-term survival even after recurrence. However, complications may occur and multimodality approaches are needed for the survivors.